(untitled) (Jalalabad Medical Journal, 2025)
Dementia is the loss of memory and other cognitive abilities severe enough to interfere with day-to-day functioning. It is brought on by an alteration in the nervous system. Although there are several varieties of dementia, Alzheimer’s disease is the most prevalent. Pharmacological agent cholinesterase inhibitors (ChEIs) have been used globally and have demonstrated efficacy in treating dementia patients. The objective of the study was to evaluate the efficacy and tolerability of donepezil for patients with mild to moderate dementia. This interventional study was conducted from July 2017 and June 2018 in neurology, psychiatry, and medicine outdoor of Sylhet MAG Osmani Medical College Hospital, Sylhet. A total of 102 dementia patients were enrolled by purposive sampling. Patients diagnosed with mild-to-moderate dementia, regardless of gender, were prescribed donepezil 5 mg once daily for 20 weeks. Initially, 110 patients were included; however, finally, data from 102 patients were analysed. Cognitive functions of the patients were measured using the Mini-Mental State Examination (MMSE) score at the completion of the fourth, twelfth, and twentieth weeks. Evaluations of safety and tolerance of donepezil include keeping monitor of and documenting any adverse effects following the treatment. The mean MMSE score at the start of the donepezil treatment was 15.05±3.49. At four, twelve, and twenty weeks of treatment, the scores were raised significantly (p<0.001). The percentage change in the MMSE score developed significantly (p<0.001) over the course of the 20-week treatment. As therapy progressed, adverse effects decreased significantly (p<0.05). Donepezil at the prescribed dosage is effective and well-tolerated for mild to moderate dementia. Jalalabad Med J 2024; 21 (2); 57-61